Analysis of the molecular diversity of Mycobacterium tuberculosis isolates from patients attending central referral hospital, East Sikkim based on the IS6110 element - Tewari, Uttejna; Adhikari, Luna; Khandelwal, Bidita; Bhandari, Sameer (International Journal of Research in Medical Sciences, 2022)
Background: Using the marker IS6110, which is rated the gold standard for molecular research of Mycobacterium tuberculosis complex (MTB),this study seeks to determine the type of circulating strain of M tuberculosis complex (MTB). MTB genotype was determined from clinical samples of patients exhibiting pulmonary and extrapulmonary tuberculosis at the Central Referral Hospital, SMIMS, Sikkim. Methods: The PCR using IS6110 and 38kDa markers were used for identifying the isolates of M tuberculosis complex in LJ slants and restriction fragment length polymorphism methodology for identifying number of copies of IS6110 had been used to classify 100 M tuberculosis isolates (RFLP-PCR). Results: IS6110 comprised a number of bands ranging between 0 to 2, with the majority of isolates having a single copy, followed by two copies, and a few isolates bearing no copy. Conclusions: This study showed a low copy of IS6110 the most predominant circulating strain in the community of Sikkim with high frequency of 85% of single copy of IS6110.